Proximity risk assessment for two sensitive chemical plants based on the accident scenario consequence analysis. Issue 1 (15th July 2013) - Maria, Gheorghe; Dinculescu, Daniel; Khwayyir, Hasan Hadi Salman
ABSTRACT Petrochemical complexes include high risk interconnected plants processing large quantities of dangerous/flammable substances, complex reactors of high thermal sensitivity operated under severe conditions of high productivity and associated equipment, vessels or separation units operating at intense temperature and pressures. Such plant design/operation problems contribute quite frequently to the occurrence of small incidents or rare major accidents including domino effects. The study applies classical boiling liquid expanding vapour explosion fire and toxic puff release models to evaluate the effects and consequences of different accident scenarios involving two neighbouring risk plants, with exemplifications for the aniline and maleic anhydride synthesis plants. A proposed joint probability index of human casualties, related to thermal radiation doses and toxic material released around plants, points out the influence of production capacity and plant proximity on the severity of accident consequences and domino‐effect occurrence. © 2013 Curtin University of Technology and John Wiley & Sons, Ltd.